2012
DOI: 10.1242/jcs.111872
|View full text |Cite
|
Sign up to set email alerts
|

MDC1 and RNF8 function in a pathway that directs BRCA1-dependent localization of PALB2 required for homologous recombination

Abstract: SummaryThe PALB2 protein is associated with breast cancer susceptibility and Fanconi anemia. Notably, PALB2 is also required for DNA repair by homologous recombination (HR). However, the mechanisms that regulate PALB2, and the functional significance of its interaction with the BRCA1 breast cancer susceptibility protein, are poorly understood. Here, to better understand these processes, we fused PALB2, or the PALB2(L21P) mutant which cannot bind to BRCA1, with the BRCT repeats that are present in, and which lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 45 publications
1
47
0
Order By: Relevance
“…Subsequently, it was demonstrated that defective localization of a mutant of the PALB2 coiled-coil domain, and of RAD51 downstream, can be rescued by fusion to the BRCT repeats that normally localize BRCA1 [62]. This lends strong support to the conclusion that BRCA1 localizes PALB2.…”
Section: The N-terminus Of Palb2mentioning
confidence: 91%
See 1 more Smart Citation
“…Subsequently, it was demonstrated that defective localization of a mutant of the PALB2 coiled-coil domain, and of RAD51 downstream, can be rescued by fusion to the BRCT repeats that normally localize BRCA1 [62]. This lends strong support to the conclusion that BRCA1 localizes PALB2.…”
Section: The N-terminus Of Palb2mentioning
confidence: 91%
“…Given that PALB2 is recruited in a BRCA1-dependent manner, the question arose as to whether ubiquitin-based signaling recruits PALB2 [62]. This possibility is supported by the finding that PALB2 colocalizes with ubiquitin, detected using the FK2 antibody, following exposure to IR [62]. Similar to the result for BRCA1 [8385], RNAi-mediated depletion of RNF8 dramatically reduces IR-induced PALB2 foci [62].…”
Section: The N-terminus Of Palb2mentioning
confidence: 99%
“…1D). Since monomeric PALB2 has been shown to possess higher activity in DNA binding and RAD51-mediated strand invasion in vitro (37) and a monomeric PALB2 recruited to DNA sites by a fused BRCT domain is functional in HR in the cell (38), it appears that loss of BRCA1 binding is likely the cause of the reduced HR activities of the mutant proteins.…”
Section: Mutational Analysis Of the Palb2 Coiled-coil Motif-palb2mentioning
confidence: 99%
“…5A,B). RAP80, a DDR factor that binds to ubiquitin generated in a RNF8-dependent manner (Mailand et al 2007;Wu et al 2009;Zhang et al 2012) and transmits DDR signaling in somatic cells, is absent on meiotic sex chromosomes; however, it accumulates on both ends of all chromosomes regardless of the genotype of RNF8 (Fig. 5C,D).…”
Section: Rnf8-dependent Gene Activation In Germ Cellsmentioning
confidence: 99%
“…Briefly, cells were grown overnight on glass coverslips prior to transfection with siRNAs directed against LacZ (control) or RNF8 (59-GGACAAUUAUGGACAACAA-39) (Zhang et al 2012). At 48 h after transfection, cells were incubated with 10 mM BrdU for 24 h and then microirradiated (355 nm) in stripes using an ArcturusXT laser capture microdissection system (Invitrogen).…”
Section: Chip-seq Analysismentioning
confidence: 99%